A 1D:2D structured AgNW:MXene composite transparent electrode with high mechanical robustness for flexible photovoltaics. Issue 22 (23rd May 2022) - Chen, Weipeng; Zhang, Ruijia; Yang, Xia; Wang, Hongyu; Yang, Hanjun; Hu, Xiaotian; Zhang, Shaohua
Abstract : MXene nanosheets weld the wire–wire junctions of a AgNW network to improve the FTE performance, and flexible PSCs and OPVs based on AgNW:MXene FTE exhibit a champion PCE of 20.22% and 16.03%, respectively. Abstract : Flexible transparent electrodes (FTEs) are essential sections for wearable and other flexible optoelectronic devices. The application of traditional indium tin oxide (ITO) electrodes in flexible devices is limited by its poor mechanical stability and expensive manufacturing equipment costs. In this work, composite FTEs are achieved by combining one-dimensional silver nanowires (AgNWs) with two-dimensional transition-metal carbide (Ti3 C2 T x MXene). The one and two-dimensional (1D:2D) structured composite AgNW:MXene FTE is generated under electrostatic interaction. 2D MXene nanosheets fill the voids of the AgNW networks and weld the wire–wire junctions by the effect of capillary force. The AgNW:MXene FTEs obtain superb photoelectric performance with a low sheet resistance of 10.91 Ω sq −1 and high transmittance of 82.84%. Besides, the AgNW:MXene FTEs show high mechanical robustness after 1000 bending tests at a curvature radius of 5 mm and long-term stability (60% relative humidity and 120 °C). Eventually, the AgNW:MXene FTEs are integrated into 0.1 cm 2 perovskite solar cells (PSCs) and organic photovoltaics (OPVs), exhibiting a high power conversion efficiency (PCE) of 20.22% and 16.03%, respectively. The stability and mechanical properties of the corresponding flexible devices are also improved.